Amino acid and fatty acid profiles of perennial Baki™ bean - Craine, Evan B.; Barriball, Spencer; Şakiroğlu, Muhammet; Peters, Tessa; Schlautman, Brandon (Frontiers in Nutrition, 2024)
To realize the potential of sainfoins to contribute to sustainable agriculture and expand on demonstrated uses and benefits, de novo domestication is occurring to develop perennial Baki™ bean, the trade name used by The Land Institute for pulses (i.e., grain legumes) derived from sainfoins. The objective of this study was to characterize amino acid and fatty acid profiles of depodded seeds from commercial sainfoin (Onobrychis viciifolia) seed lots, and compare these results with data published in the Global Food Composition Database for Pulses. The fatty acid profile consisted primarily of polyunsaturated fatty acids (56.8%), compared to monounsaturated (29.0%) and saturated fatty acids (14.2%), and n-3 fatty acids (39.5%), compared to n-9 (28.4%) and n-6 (17.6%) fatty acids. The essential fatty acid linolenic acid (18:3 n-3) was the most abundant fatty acid (39.2%), followed by oleic acid (18:1 cis-9) (27.8%), and the essential fatty acid linoleic acid (18:2 n-6) (17.3%). The amino acid profile consisted primarily of the nonessential amino acids glutamic acid (18.3%), arginine (11.6%), and aspartic acid (10.8%), followed by the essential amino acids leucine (6.8%), and lysine (5.8%). Essential amino acid content met adult daily requirements for each amino acid. This indicates that sainfoin seeds may be a complete plant protein source. However, further research is necessary to better understand protein quality, defined by protein digestibility in addition to the amino acid profile. By demonstrating favorable fatty acid and amino acid profiles to human health, these results contribute to a growing body of evidence supporting the potential benefits of perennial Baki™ bean, a novel, perennial pulse derived from sainfoins.